Pengujian Determinan Kinerja Pegawai - Muhammad Donal Mon; Dinda Suci Ramadhani (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This research to find out what factors can affect employee performance. The independent variables in this research consist of motivation, work environment, leadership, teamwork and work discipline, and the dependent variable is employee performance. This study used 147 questionnaires, only 143 questionnaires that could be used as research samples. The questionnaires obtained were processed with SPSS to test the research on respondents who work as teachers at Elementary School in Tanjungpinang Barat. The results of the study show that employee motivation, leadership and work discipline have a significant positive effect on employee performance. However, the work environment and teamwork have no significant effect on employee performance.